36
$\begingroup$

Let $(W_t)$ be a standard Brownian motion, so that $W_t \sim N(0,t)$. I'm trying to show that the random variable defined by $Z_t = \int_0^t W_s \ ds$ is a Gaussian random variable, but have not gotten very far.

I tried approximating the integral by a Riemann sum: choose $\delta, M$ such that $M\delta = t$, then the integral is approximated by $$ \sum_{k=0}^{M-1} (W_{(k+1)\delta} - W_{k\delta} )\delta = \delta \sum\limits_{k=0}^{M-1} X_k $$ where using standard properties of the Brownian motion, the $X_k$'s are independent identically distributed $N(0, \delta)$ random variables. So I find that $Z_t$ is approximated by a random variable with distribution $ N(0, M\delta^3) = N(0,t\delta^2) $. Now letting $ \delta \to 0$, I find the variance of $Z_t$ is also $0$, which does not make sense to me.

Any help is appreciated!

$\endgroup$
1
  • 4
    $\begingroup$ That's not the Riemann sum; you want $\sum_{k=0}^{M-1} \delta W_{k\delta}$. $\endgroup$ Nov 24, 2012 at 20:28

3 Answers 3

37
$\begingroup$

First of all, the Riemann sum is given by

$$\sum_{k=0}^{M-1} W_{k \delta} \cdot (\delta (k+1)-\delta k).$$

Note that this expression does not equal

$$\sum_{k=0}^{M-1} (W_{(k+1)\delta}-W_{k \delta}) \cdot \delta.$$


Let $t_k := \delta \cdot k$, then

$$\begin{align} G_M &:= \sum_{k=0}^{M-1} W_{k \cdot \delta} \cdot (t_{k+1}-t_k) =\ldots= \sum_{k=0}^{M-1} (W_{t_{k-1}} - W_{t_k}) \cdot t_k + W_{t_{M-1}} \cdot t \\ &= \sum_{k=0}^{M-1} (W_{t_{k-1}}-W_{t_k}) \cdot (t_k-t) \end{align}$$

where $t_{-1}:=0$. Clearly, $G_M$ is Gaussian, $\mathbb{E}G_M=0$ and (using the independence of the increments)

$$\begin{align*} \mathbb{E}(G_M^2)& = \sum_{k=0}^{M-1} (t_k-t)^2 \cdot \underbrace{\mathbb{E}((W_{t_k}-W_{t_{k-1}})^2)}_{t_k-t_{k-1}} \\ &\to \int_0^t (s-t)^2 \, ds \quad \text{as} \, \, M \to \infty. \end{align*}$$

Hence, as $G_M \to Z_t$ as $M \to \infty$ almost surely, we conclude that $Z_t$ is Gaussian with mean $0$ and variance $\int_0^t (s-t)^2 \, ds$ (see this question for further details).

Remark: In fact, the statement holds in a more general setting. The random variable $Y_t := \int_0^t X_s \, ds$ is Gaussian for any (measurable) Gaussian process $(X_t)_{t \geq 0}$, see this question.

$\endgroup$
16
  • 4
    $\begingroup$ @Jonas: The factors in the cross terms are indepedent, aren't they? $\endgroup$ Nov 25, 2012 at 0:05
  • 3
    $\begingroup$ @Matteo Note that $W_{k \cdot \delta} = W_{t_k}$. Thus, $$\begin{align*} \sum_{k=0}^{M-1} W_{k \cdot \delta} (t_{k+1}-t_k) &= \sum_{k=0}^{M-1} W_{t_k} \cdot t_{k+1} - \sum_{k=0}^{M-1} W_{t_k} \cdot t_k \\ &= \sum_{k=1}^{M} W_{t_{k-1}} \cdot t_{k} - \sum_{k=0}^{M-1} W_{t_k} \cdot t_k \\ &= W_{t_{M-1}} \cdot t_{M} + \sum_{k=0}^{M-1} (W_{t_{k-1}}-W_{t_k}) \cdot t_k \end{align*}$$ where we used in the last step $W_{t_0}=0$. $\endgroup$
    – saz
    Dec 7, 2013 at 20:03
  • 2
    $\begingroup$ @Calculon Where have I claimed/used this? Anyway, we can apply Fubini's theorem to interchange expectation and integration: $$\mathbb{E} \left( \int_0^t W_s \, ds \right) = \int_0^t \mathbb{E}(W_s) \, ds=0.$$ $\endgroup$
    – saz
    Mar 18, 2015 at 19:37
  • 1
    $\begingroup$ @Calculon "Expectation of the square of the integral"..? Could you please be a bit more specific: Which integral are you exactly talking about? And what do you (exactly) want to know? In my answer, I have calculated $\mathbb{E}(G_M)$ and $\mathbb{E}(G_M^2)$. Since $G_M$ is a finite sum for each $M$, we don't need to interchange limit and expectation. $\endgroup$
    – saz
    Mar 18, 2015 at 19:49
  • 1
    $\begingroup$ @Calculon I see. Well, it is not obvious that $\mathbb{E}(G_M^2)$ converges to $\mathbb{E}(Z_t^2)$. In this particular case, this follows from the fact that $G_M$ and $Z_t$ are Gaussian. (Mind: If a sequence $(G_n)_n$ converges pointwise to some random variable $Z$ and $\mathbb{E}(G_n^2)$ converges to some constant $c$, then in general $c \neq \mathbb{E}(Z^2)$. However, under the additional assumption that $G_n$ and $Z$ are Gaussian, we have $c= \mathbb{E}(Z^2)$.) $\endgroup$
    – saz
    Mar 18, 2015 at 20:06
17
$\begingroup$

I just found out that we can use the following fact:

If $f:[0,T] \rightarrow [0,T]$ is continuous and deterministic, then \begin{equation} \int_{0}^T \bigg( \int_{0}^T f(s,t) \,dW_s \bigg) \,dt = \int_{0}^T \bigg( \int_{0}^T f(s,t) \, dt \bigg) \,dW_s. \end{equation} Hence (I suppose that it works for piecewise continuous functions), \begin{eqnarray} \int_{0}^T W_t \,dt & = & \int_0^T \int_0^T \mathbf{1}_{[0,t]} (s) \,dW_s \,dt \\ & = & \int_0^T \int_0^T \mathbf{1}_{[0,t]} (s) \,dt \,dW_s\\ & = & \int_0^T T-s \,dW_s\\ & \sim & N \bigg( 0, \int_{0}^T (T-s)^2 \,ds \bigg). \end{eqnarray}

$\endgroup$
2
  • 4
    $\begingroup$ This is the "stochastic Fubini theorem" or "Fubini's theorem for stochastic integrals." $\endgroup$
    – jmbejara
    Feb 6, 2015 at 3:29
  • 1
    $\begingroup$ fuar that's a great solution $\endgroup$
    – Debreu
    Sep 13, 2017 at 6:12
7
$\begingroup$

This is an old question, but it may be worth providing a better answer:

Let $\phi(Y,t,\omega)$ be the conditional characteristic function $\mathbb{E}[\exp(i\omega Y_T)|Y_t=Y] $. By the law of iterated expectations this quantity is a martingale. It is then straightforward to derive a partial differential equation for $\phi$ using Ito's lemma and setting the drift to zero. It will become apparent that the solution takes a Gaussian form.

$\endgroup$
1
  • 18
    $\begingroup$ Using a hammer to kill a fly does not necessarily makes for "better" answers. $\endgroup$
    – Did
    Jan 1, 2014 at 17:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.